Uncovering the Efficacy and Mechanism of Zhenwu Decoction for Hypothyroidism Based on Non-Targeted Metabolomics - Wang Y; Li Y; Tang M; Zhang L; Zhu S (Drug Design, Development and Therapy)
Yuhan Wang,1 Yancun Li,1 Mengyao Tang,2 Luhan Zhang,1 Shu Zhu1 1School of Traditional Chinese Medicine, Shandong University of Traditional Chinese Medicine, Shandong, People’s Republic of China; 2Yiyuan County Traditional Chinese Medicine Hospital, Shandong, People’s Republic of ChinaCorrespondence: Shu Zhu, Email drzhushu@163.comBackground: Hypothyroidism, a systemic hypometabolic syndrome from deficient thyroid hormone synthesis/utilization, has high prevalence and complex mechanisms. Levothyroxine-based lifelong therapy risks neurocognitive/metabolic complications and iatrogenic pathologies (eg, osteoporosis, hepatocardiac dysfunction). Zhenwu Decoction (ZW), a classical multi-target herbal formulation, shows therapeutic potential but requires mechanistic clarity on thyroid restoration to enable standardized translation.Objective: To investigate ZW’s therapeutic mechanisms in hypothyroidism via serum metabolomics and pathway analysis.Methods: Twenty-seven Wistar rats were randomly divided into three groups: control group (n=9), PTU model group (n=9), and Zhenwu Tang group (n=9). The hypothyroidism rat model was induced by administering propylthiouracil (PTU) by gastric gavage for 4 weeks in the PTU model and Zhenwu Tang groups, while the control group received no treatment. Subsequently, the Zhenwu Tang group underwent a 3-week herbal medicine intervention. Multidimensional validation (including phenotypic monitoring, ELISA for FT4/TSH, and HE staining) was performed to confirm the successful establishment of the model and to evaluate the therapeutic efficacy of Zhenwu Tang (ZW). Untargeted UPLC-MS/MS metabolomics was performed to identify differential metabolites (VIP > 1, p < 0.05), and MetaboAnalyst 5.0 was used to map key pathways.Results: ZW can significantly improve systemic indicators (body weight, anal temperature, feeding behavior) in hypothyroid rats. It remarkably improves the histopathological features of the thyroid gland, approaching the structure of the normal group. In addition, ZW can significantly regulate serum thyroid hormone levels (decrease TSH and increase FT4), approaching normal levels.47 metabolites (eg, L-proline, fumaric acid, estradiol) and 7 pathways (thermogenesis, cholesterol metabolism) were identified. ZW corrected metabolic dysfunction through multi-target regulation.Conclusion: ZW exerts therapeutic effects by modulating glucose-6-phosphate, bile acids, and critical metabolic pathways, thereby advancing our understanding of hypothyroidism pathophysiology and underscoring its potential for clinical translation and therapeutic development.Keywords: hypothyroidism, Zhenwu decoction, metabolomics, traditional Chinese medicine, metabolic mechanism